HRM practices during the COVID-19 pandemic: Lessons from a small island tourism destination - Zopiatis, Anastasios; Pericleous, Katerina; Shieh, Chich Jen (My University, 2024)
The hospitality industry is facing unprecedented operational and strategic challenges in dealing with COVID-19. Surfing through uncharted territories and guided by the narrative of the existing crisis management conceptual capital, stakeholders strive to mitigate the pandemic’s negative externalities, and ensure the continuity of the industry. Despite the plethora of recently published material, paradoxically, the pandemic’s effect on the industry’s workforce, the determining factor in all attempts to rebound to normality, has received marginal attention. In response, and by espousing a quantitative methodology, this study sets out to investigate the link between organizational response and support measures on one side, and employees’ organizational commitment, job insecurity, COVID-19-induced stress, and subsequent turnover intentions, on the other. Furthermore, vaccinations are investigated as a control variable to measure the effects on the human resources issues under investigation. Theoretical and practical implications, of importance to industry stakeholders, are discussed.
Keywords: COVID-19; turnover intention; vaccinations; organizational commitment; organizational response; stress; job insecurity